PERLINDUNGAN HUKUM TERHADAP HAK-HAK WARGA BINAAN PEREMPUAN HAMIL DAN MELAHIRKAN DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIB PADANG - Nadia Hilmy, Nurlinda Yenti dan (Normative Jurnal Ilmiah Hukum, 2024)
Legal protection for pregnant and giving birth female inmates has not been specifically regulated in statutory regulations, but we can see this in Article 20 of Government Regulation Number 32 of 1999 concerning Requirements and Procedures for Implementing the Rights of Correctional Inmates. However, the implementation of these rights is limited by the availability of inadequate facilities and infrastructure as well as human resources. The formulation of the problem is how to legally protect the rights of inmates who are pregnant and giving birth, what are the obstacles in legal protection of the rights of inmates who are pregnant and giving birth and what are the efforts in legal protection of the rights of inmates who are pregnant and giving birth in women's prisons? Class IIB Padang. This research uses a sociological juridical approach. Discussion The results of the research show that legal protection for the rights of pregnant and giving birth female inmates based on Government Regulation Number 32 of 1999 concerning Requirements and Procedures for Implementing the Rights of Correctional Inmates has been implemented but is not yet optimal, because there are several obstacles. both internal and external constraints. The internal obstacles are the lack of quantity and quality of officers in implementing the rights of pregnant and giving birth inmates, inadequate facilities and infrastructure and limited budget or funds. Meanwhile, the external obstacle is the lack of community participation or support for inmates who have returned to society. Meanwhile, the efforts made are to improve the abilities or skills of prison officers through education and training, save budgets, sell the results of the skills of inmates and can carry out budget revisions and submit proposals for the fulfillment of facilities and infrastructure through preparing a plan for state property needs for. Meanwhile, external efforts include conducting outreach and providing understanding to the public regarding correctional institutions, especially regarding the existence of ex-convicts who need encouragement to return to society so that they do not repeat criminal acts again.